EDP Baixo Sabor: Construction and Reservoir Filling Phases – Wolf, (Canis lupus) Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) [camera-trapping] - [2011-2014] ... - Mota, Paulo; Vingada, José Vítor; Ferreira, Joana; Diogo, Hugo Manuel; Morgado, Rui Guilherme; Rodrigues, Pedro; Garrido, Nuno; Eira, Catarina Isabel; Pinto, Nuno; Marques, Carina (EDP - Energias de Portugal, 2020)
The dataset contains records of Iberian Wolf (Canis lupus), Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) collected in the lower valley of River Sabor (NE Portugal), in the scope of the long-term Ecological Monitoring Program (PME) of the Baixo Sabor Hydroelectric Dams (AHBS), promoted by EDP – Energias de Portugal, S.A. This dataset includes results of surveys made in and around the area affected by the dams, from March 2011 to August 2014. Sampling was performed by camera-traps distributed along the lower Sabor river valley (and some tributaries) and in rivers Maçãs and Angueira, from the river mouth up to 42 km upstream. The presence and identity of the target species were assessed by observing the photos taken with the cameras. A total of 3879 photos of the target species were obtained (2892 of Sus scrofa, 982 of Capreolus capreolus, and 5 of Canis lupus). These numbers do not necessarily refer to different individuals. ...